2019
DOI: 10.3390/nu11030642
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status, Calcium Intake and Risk of Developing Type 2 Diabetes: An Unresolved Issue

Abstract: The relationship between vitamin D status, calcium intake and the risk of developing type 2 diabetes (T2D) is a topic of growing interest. One of the most interesting non-skeletal functions of vitamin D is its potential role in glucose homeostasis. This possible association is related to the secretion of insulin by pancreatic beta cells, insulin resistance in different tissues and its influence on systemic inflammation. However, despite multiple observational studies and several meta-analyses that have shown a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 88 publications
3
49
0
3
Order By: Relevance
“…Therefore, we cannot exclude that, in the studied women, such significant changes in 25(OH)D concentrations after the intervention were related to changes in CTX levels via the modification of energy profile (we can assume that observing the reduction in fat mass). Other authors previously confirmed the associations of 25(OH)D concentrations with adiposity indices [18,19].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Therefore, we cannot exclude that, in the studied women, such significant changes in 25(OH)D concentrations after the intervention were related to changes in CTX levels via the modification of energy profile (we can assume that observing the reduction in fat mass). Other authors previously confirmed the associations of 25(OH)D concentrations with adiposity indices [18,19].…”
Section: Discussionsupporting
confidence: 55%
“…Calciotropic actions are related to bone mass regulation procedures. However, there is also evidence that vitamin D, through vitamin D receptors, plays an important role in many other tissues, including skeletal muscles [16] and adipose tissue [17], and in the regulation of glucose and insulin homeostasis [18]. Moreover, low serum calcidiol (25(OH)D) concentrations, which express the body's vitamin D status, accompany many types of diseases e.g., cancer, cardiovascular disease, and metabolic and autoimmune disorders [19].…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of SUCRA, vitamin D supplementation was the best for reducing FPG and improving HOMA-IR compared with the effects of the other nutritional strategies, and magnesium supplementation ranked second. Vitamin D, also known as calciferol, is mainly active in the body as 25-hydroxyvitamin D (25(OH)D), which is often used as the best indicator for measuring vitamin D levels [40]. Vitamin D deficiency is a common phenomenon after pregnancy; a study showed that at 25-28 weeks of gestation, the concentration of 25(OH)D in GDM patients is significantly reduced [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of calcium supplementation on MetS remains poorly established. 24 The conflicting results for calcium supplementation, which appears to decrease the level of insulin resistance and increase the serum calcium levels, appears to be associated with a higher level of insulin resistance, implying a more complex pathomechanism than that only merely reflected by the serum calcium levels.…”
Section: Discussionmentioning
confidence: 99%